Convalescent plasma treatment in severely immunosuppressed patients hospitalized with COVID-19: an observational study of 28 cases. Issue 4 (3rd April 2022) - Ljungquist, Oskar; Lundgren, Maria; Iliachenko, Elena; Månsson, Fredrik; Böttiger, Blenda; Landin-Olsson, Mona; Wikén, Christian; Rosendal, Ebba; Överby, Anna K.; Wigren, Byström J.; Forsell, Mattias N. E.; Kjeldsen-Kragh, Jens; et al.
Abstract: Background: Immunosuppressed patients are particularly vulnerable to severe infection from the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), risking prolonged viremia and symptom duration. In this study we describe clinical and virological treatment outcomes in a heterogeneous group of patients with severe immunosuppression due to various causes suffering from COVID-19 infection, who were all treated with convalescent plasma (CCP) along with standard treatment. Methods: We performed an observational, retrospective case series between May 2020 to March 2021 at three sites in Skåne, Sweden, with a population of nearly 1.4 million people. All patients hospitalized for COVID-19 who received CCP with the indication severe immunosuppression as defined by the treating physician were included in the study ( n = 28). Results: In total, 28 severely immunocompromised patients, half of which previously had been treated with rituximab, who had received in-hospital convalescent plasma treatment of COVID-19 were identified. One week after CCP treatment, 13 of 28 (46%) patients had improved clinically defined as a decrease of at least one point at the WHO-scale. Three patients had increased score points of whom two had died. For 12 patients, the WHO-scale was unchanged. Conclusion: As one of only few studies on CCP treatment of COVID-19 in hospitalized patients with severe immunosuppression, this study adds descriptive data. The study design prohibits conclusions on safety and efficacy, and the results should be interpreted with caution. Prospective, randomized trials are needed to investigate this further.